6 Barriers and incentives to in-situ simulation on the delivery suite. (17th November 2016) - Pritchett, CSA; King, H; Nash, S; Rajasri, A; Nelson, Z; Cripps, A; Harris, S; Langford, R
Abstract : Simulation is a widely adopted method of teaching and training within the NHS. Notably, evidence linking simulation training to improved patient outcome exists within delivery suite based training. 1–3 At the Royal Cornwall Hospital (RCH) we have delivered in-situ simulation and simulation-based multidisciplinary training days for delivery suite personnel for 6 years. Despite this tradition, we have experienced difficulties in embedding in-situ simulation. This quality improvement project assessed the barriers and incentives towards simulation from all professional groups on delivery suite. Methods: Questionnaires were designed to capture professional role, experience, confidence in basic skills and obstetric emergencies along with anxieties, barriers and incentives to participation in simulation. Questions relating to confidence used a 10 point Lickert scale to allow comparison between professional groups. The questionnaire was completed anonymously by participants. Results: 106 completed questionnaires were analysed. Response rates were: 41 midwives (89%), 7 midwifery coordinators (100%), 20 obstetric doctors (80%), 26 anaesthetic doctors (96%), 4 staff nurses (100%) and 7 maternity support workers (47%). Anaesthetists were the most confident and midwives the least confident of all registered professionals in performing an 'A-E assessment' and managing acute maternal compromise. Midwives were the most anxious about participating in simulation. 5 self-reported barriers to participation were identified by midwives: 1) Feeling like it's an assessment, 2) Feeling embarrassed or nervous, 3) Being asked to play a role not their own, 4) Unrealistic feel/scenario 5) Excessive workload. 80% of midwives said that further A–E assessment training would encourage them to participate in simulation. Conclusions: We have identified 5 self-reported barriers to in-situ simulation on the delivery suite. This survey has allowed us to modify our in-situ training to improve engagement. We have introduced the Maternal Acute Illness Management course to improve staff confidence in assessing and managing the acutely unwell parturient. References: Phipps MG, Lindquist DG, McConaughey E, et al . Outcomes from a labor and delivery team training program with simulation component. Am J Obstet Gynecol 2012;206 (1):3–9. Draycott TJ, Crofts JF, Ash JP, et al . Improving neonatal outcome through practical shoulder dystocia training. Obstet Gynecol 2008;112 (1):14–20. Draycott T, Sibanda T, Owen L, et al . Does training in obstetric emergencies improve neonatal outcome? BJOG 2006;113 (2):177–82.